Dark money, super PACs, and the 2012 election - Smith, Melissa M., 1963- (Lexington studies in political communication., 2014)
This book helps identify and explain how the new federal campaign finance rules changed the way campaigns were run and paid for in 2012, along with shifting the balance of power from political parties to third-party interest groups.